Cycle Safety. Reducing the Crash Risk. October 2009. - Turner, Shane; Binder, Shane; Roozenburg, Aaron (My University, 2009)
The crash benefits to cyclists of reducing traffic volumes and speeds, and constructing cycle lanes and intersection treatments have been investigated during 2006 and quantified based on overseas research and data collected within Christchurch, Palmerston North and Nelson. It was found that cycle lane facilities provided a reduction in cycle crashes of around 10%. Becuase no suitable New Zealand data is available on the safety of cycle paths and speed reduction measures, so the discussion focuses on international research findings.
Keywords: Individualverkehr; Fahrradverkehr; Verkehrssicherheit; Fahrradweg; Fahrradinfrastruktur; Studie; Radverkehrsanlage; Radfahrstreifen; Unfallvermeidung